Kinerja Portofolio Investasi Saham Dengan Standar Deviasi Untuk Mengukur Volatilitas Pasar Ekuitas Pada Pasar Modal Indonesia - Amir Paisal; Alifia Rachma Suhandoko; Dinah Siti Rubai’ah Adawiyah; Pebi Pebrianti; Ujang Suherman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Indonesian capital market is a dynamic and challenging area for investment stakeholders, especially stock portfolio holders. This objective is to measure and analyze the performance of stock investment portfolios using standard deviation as a key indicator to measure equity market volatility in the Indonesian capital market. The writing method used is a descriptive method using standard deviation. The result of the standard deviation shows that the higher the investment risk between risk and return to compensate the return corresponding to the greater level of risk taken, but also increases the potential loss. The performance of the stock investment portfolio in 2022 can be said to be good. This can be seen from the growth in portfolio value that continues to increase from month to month. The portfolio's average return on investment (IRR) is 8%.